ATP-Bioluminescence and Conventional Microbiology for Hygiene Evaluation of Cutting Room Surfaces in Poultry Slaughterhouse. - Rodrigues, Laura Beatriz; dos Santos, Luciana Ruschel; Rizzo, Natalie Nadin; Ferreira, Daiane; de Oliveira, Amauri Picollo; Levandowski, Rafael; Webber, Bruna; do Nascimento, Vladimir Pinheiro (Acta Scientiae Veterinariae, 2018)
Background: The hygiene procedures in poultry slaughterhouses consist in the use of hot water, detergent and sanitizing, configuring Sanitation Standard Operating Procedure (SSOP). These actions control contamination in food processing environments, especially by pathogenic microorganisms, which cause diseases with impact on public health and economic losses. The microbiological control of aerobic mesophiles, Staphylococcus aureus and Escherichia coli, are used as indicators of contamination. The hygienic-sanitary conditions on the surfaces of the poultry slaughterhouse cuttting room were evaluated, before and after cleaning and sanitizing procedures. Materials, Methods & Results: Conventional microbiology (Rodac plates and sponge for quantification of aerobic mesophiles, Staphylococcus aureus and Escherichia coli) and ATP-Bioluminescence were used to analyze the action of hot water and the active principles peracetic acid, quaternary ammonia and biguanide in the standard pre-operational hygiene procedure in the cutting room of the poultry slaughterhouse under Federal Inspection with slaughter capacity of more than 20.000 birds/h. The evaluations were performed on three lines of chicken thigh cuts at the same time and in a completely randomized manner on stainless steel surfaces, polyurethane belts and polyethylene boards. Samples were made in four replicates at the three surface totaling 108 assay for each microorganism. The samples were collected at the end of the cutting process, before and after washing the surfaces with hot water (between 45 and 50ºC) and after sanitization with 0.5% peracetic acid, 2% quaternary ammonia and 1% biguanide. The ATP-Bioluminescence method detected organic matter at all collected points and Rodac plates allowed a better recovery of microorganisms than sponges for quantification of aerobic mesophiles, E. coli and S. aureus. There was a reduction of contamination after the action of hot water and, after using quaternary ammonia and peracetic acid, there was no isolation of E. coli and S. aureus on all evaluated surfaces. Discussion: The use of different methods of analysis for monitoring the hygiene and sanitary status of contact surfaces with chicken cuts allows greater flexibility in relation to hygiene control. The use of the bioluminescent ATP detection method allows detecting in seconds extremely low levels of contamination, allowing a quick determination of the cleaning efficiency on the surfaces and evaluation of the hygiene programs. Conventional microbiology methods, on the other hand, provide indicators of contamination by different microorganisms on food contact surfaces. Both are applicable in SSOP monitoring programs and sanitary conditions of the contact surfaces in food producing establishments. The significant reduction of microorganisms on surfaces after cleaning, found in this study, demonstrates the importance of operational hygiene in the maintenance of microbial contamination below the recommended limits, and to reconcile the ATP-Bioluminescence methodologies and Rodac plates can bring benefits to the control of this contamination, and the use of ATP-bioluminescence makes possible taking immediate corrective measures after the evaluation of sanitation procedures. Keywords: ATP-Bioluminescence, Rodac plates, Escherichia coli, mesophiles, Staphylococcus aureus.